2007
DOI: 10.1038/ja.2007.27
|View full text |Cite
|
Sign up to set email alerts
|

Selective and Potent In Vitro Antimalarial Activities Found in Four Microbial Metabolites

Abstract: Antimalarial activities have been identified in four microbial metabolites through a screening programme of existing compounds in the Kitasato Institute chemical library. Hedamycin showed selective and potent activity against both drug-resistant and drug-sensitive strains of Plasmodium falciparum. Simaomicin a exhibited remarkably strong antimalarial activity, although its activity against a drug-resistant strain was weaker than that against a drugsensitive strain. The antimalarial effects of triacsins C and D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
29
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 13 publications
(6 reference statements)
1
29
0
Order By: Relevance
“…[3][4][5][6][7][8] Recently, we have isolated some tropolone compounds from a culture broth of Penicillium sp. FKI-4410.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8] Recently, we have isolated some tropolone compounds from a culture broth of Penicillium sp. FKI-4410.…”
Section: Introductionmentioning
confidence: 99%
“…From the screening of hundreds of natural antibiotics in the Kitasato Institute for Life Sciences Chemical Library [19], we found the inhibitory activity of GS for Escherichia coli cytochrome bd. Recent studies have shown that GS analogs can be designed with the markedly improved therapeutic index, suggesting the possibility of GS derivatives as potent broad-spectrum antibiotics [9,[20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8] In the course of our screening, we found borrelidin, produced by an actinomycete strain OM-0060, that proved to be more potent than chloroquine or artemether (using in vivo oral administration) against drug-resistant P. yoelii. 6 The reported biological activities of borrelidin are suggested to be the results of protein synthesis inhibition, caused by the effect on threonyl-tRNA synthetase.…”
mentioning
confidence: 97%